Epidemiology of gastrointestinal cancers in the hospital of Tambohobe Fianarantsoa, Madagascar - Ranaivomanana, Mampionona; Rafaralahivoavy, Tojo; Razafimahefa, Joelle; Rakotovao, Anicet M.; Rakotoarivelo, Rivo A.; Razafimahefa, Hélio S.; Rafaramino, Florine (International Journal of Research in Medical Sciences, 2019)
Background: Gastrointestinal cancers are among the top 10 cancers and causes of cancer death worldwide. Given the absence of cancer registry in Madagascar and absence of epidemiological study of gastrointestinal cancer in the province of Fianarantsoa, our aim was to describe the epidemiological aspect of gastrointestinal cancers at the University Hospital of Tambohobe Fianarantsoa. Methods: Authors have conducted a descriptive retrospective study over a three-year period from January 1, 2015 to December 31, 2017 at the University Hospital of Tambohobe Fianarantsoa (in oncology, internal medicine and visceral surgery departments). The variables analyzed were age, gender, tumor location. Results: Authors have collected 74 cases of gastrointestinal cancers. There were 46 males 62.16% and 28 females 37.84%. The mean age was 56.30±12.10 years old. The predominant age groups were 45-55 years. Authors found colorectal cancer in 43%, followed by liver carcinoma in 19%, then pancreatic cancer 14%, esophageal cancer 13%, gastric cancer 8%, duodenum cancer 3%. Conclusions: Gastrointestinal cancers at the hospital of Tambohobe Fianarantsoa affect young people, especially the male gender with a predominance of colorectal and liver cancer.So, it is important to continue the vaccination against hepatitis viral B infection and to implement a colorectal cancer screening program.